Selenium Biofortification Modulates Plant Growth, Microelement and Heavy Metal Concentrations, Selenium Uptake, and Accumulation in Black-Grained Wheat - Liu, Yuxiu; Huang, Shuhua; Jiang, Zonghao; Wang, Yizhao; Zhang, Zhengmao (Frontiers in Plant Science, 2021)
Selenium (Se)-enriched wheat is a source of Se supplementation for Se-deficient populations, and Se content can be improved by agronomic biofortification. Thus, black-grained wheat and white-grained wheat (as the control) were grown in soils that naturally contained different concentrations of Se (11.02, 2.21, 2.02 and 0.20 mgkg-1, respectively). Then, a field experiment was conducted to assess agronomic performance, concentration of microelements and heavy metals, and uptake and distribution of Se in the black-grained wheat under the application of Se ore powder. The results showed that the grain yield and grain Se concentration of wheat were significantly increased and decreased from high-Se to low-Se area, respectively. Higher grain yield and crude protein content was observed in Se-rich areas. Soil application of Se ore powder increased wheat grain yield and its components (biomass, harvest index, grain number and thousand kernels weight). Concentrations of Zn, Fe, Mn, total Se and organic Se in grains of wheat were also increased, but the Cu concentration was decreased. Concentrations of Pb, As, Hg and Cr in wheat grains were below the China food regulation limits following soil application of Se ore powder. Se ore powder treatment increased the uptake of Se in various parts of wheat plants compared with the control. More Se accumulation was observed in roots following Se ore powder application, with a smaller amount in grains. In addition, black-grained wheat had significantly higher concentrations of Zn, Fe and Mn, and accumulated more Se in grains and shoots and less Se in roots, compared with the control. The results indicate that wheat grown in Se-rich areas increases its grain yield and crude protein content. Soil application of Se ore powder promotes wheat growth and grain yield. The black-grained wheat accumulated more Se in grains and had a higher concentration of organic Se in grains than the white-grained wheat. In conclusion, the application of Se ore powder from Ziyang as Se-enriched fertilizer could be a promising strategy for Se biofortification for wheat and black-grained wheat is the most Se-rich potential genotype.